Inertia or inaction? blood pressure management and cardiovascular risk in diabetes - Owen, A.; Retegan, C.; Rockell, M.; Jennings, G.; Reid, Christopher (Wiley-Blackwell Publishing Asia, 2009)
Diabetes is a significant risk factor for cardiovascular disease (CVD), but the presence of comorbidities, such as hypertension, markedly increases CVD risk. The aim of the present study was to determine the effectiveness of hypertension management in patients with diabetes. The cvTRAC Study was a cross-sectional study of CVD risk factors in primary care practices across Australia. General medical practitioners enrolled patients they considered to be at increased risk of CVD and reported on cardiovascular disease history, CVD risk factor levels and current therapy. In all, 9857 men and 8332 women with diabetes participated in the study, with > ;85% having at least two CVD risk factors in addition to diabetes and 68% having a history of hypertension. Lost therapeutic benefit in diabetes patients with hypertension was seen in those who were failing to meet targets on antihypertensive drug therapy (therapeutic inertia: > ;73% of the hypertensive cohort), with a smaller proportion accounted for by those who met prescribing guidelines but were not being treated pharmacologically (treatment gap: 5.4% of the hypertensive cohort). Lack of compliance with lifestyle guidelines was estimated to account for over 8% of those not meeting blood pressure targets. Age (odds ratio (OR) 0.983, 95% confidence interval (CI) 0.980-0.986; P < 0.001), compliance with physical activity guidelines (OR 1.219, 95% CI 1.088-1.366; P = 0.001) and compliance with dietary guidelines (OR 1.298, 95% CI 1.188-1.420; P < 0.001) were independent predictors of target blood pressure attainment in the diabetic population. Deficiencies in pharmacological and lifestyle-related therapeutic strategies contribute to suboptimal hypertension management in diabetes. Therapeutic inertia is a greater contributor to lost therapeutic benefit than treatment gap in this population. © 2009 Blackwell Publishing Asia Pty Ltd.